Comparison of Intraocular Pressure Before and After Silicone Oil Evacuation with Retinal Detachment History in Jakarta Hospital - Farida, Nida; Sari, Nurmila; Nugraha, Ghina Fitria (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2023)
Background: Retinal disorders are the fourth most common cause of blindness in Indonesia and one of them is retinal detachment. Vitrectomy with silicone oil (SO) tamponade is a popular technique for treating it. As a complication of using SO, intraocular pressure (IOP) can increase and usually returns to normal after evacuation of SO. However, in some conditions, such as emulsifying SO, can cause IOP to remain high even after SO evacuation has been carried out.Objective: To determine the comparison of intraocular pressure before and after evacuation of silicone oil in patients with a history of retinal detachment.Method: This study is a cross sectional with analytical reasearch. Secondary data was taken from the medical records of patients with a history of retinal detachment who underwent silicone oil evacuation performed at KMJA Jakarta Hospital.Result: 39 Respondents aged 23-69 years and 82% are male. The average length of use of SO is 9 months. It was found that the IOP decreased which was not significant in weeks 1-2 after evacuation of SO (p value 0.098) and also the increase in IOP was not significant in weeks 3-4 after evacuation of SO (p value 0.184).Conclusion: There is no significant difference in intraocular pressure before and after evacuation of silicone oil in patients with a history of retinal detachment